Antimicrobial activity of extracts of eastern North American hardwood trees and relation to traditional medicine - Omar, S. (S.); Lemonnier, B. (B.); Jones, N. (N.); Ficker, C. (C.); Smith, M. (Myron); Neema, C. (C.); Towers, G.H.N. (G. H N); Goel, K. (K.); Arnason, J.T. (J. T.) (Journal of Ethnopharmacology, 2000)
Wood and bark extracts of 14 eastern North American hardwood tree species which were used traditionally as medicine by First Nation's people were screened for antimicrobial activities with eight strains of bacteria and six strains of fungi. Eighty-six percent of the bark extracts were active against methicillin sensitive Staphylococcus aureus; 71% against Bacillus subtilus and 79% against Mycobacterium phlei. The bark extract of Juglans cinerea was active against Pseudomonas aeruginosa 187, Salmonella typhiumurium, and Klebsiella pneumoniae. The wood extracts were less active: 72% were active against S. aureus (methicillin-sensitive), 36% against B. subtilus and 43% against M. phlei. Results from antifungal tests indicated that 36% of the extracts were active against at least one fungal strain and that bark extracts were more active than wood extracts. The bark extract from Juglans cinerea had the broadest spectrum of activities against Candida albicans, Saccharomyces cerevisiae, Cryptococcus neoformans, Trichophyton mentagrophytes, Microsporum gypseum, and Aspergillus fumigatus. In general, the extracts were more active against gram positive bacteria than gram negative bacteria and against filamentous fungi than yeast-like fungi. The study also demonstrated a correlation between frequency of traditional medicinal use by the First Nations people and antimicrobial activity of extracts indicating that the traditional knowledge encompasses an understanding of aspects of chemical ecology. (C) 2000 Elsevier Science Ireland Ltd.